Characterization and thermal behavior of residues from industrial sugarcane processing - Crespi, Marisa Spirandeli [UNESP]; Martins, Quezia V. [UNESP]; de Almeida, Sonia [UNESP]; Barud, Hernane S. [UNESP]; Kobelnik, Marcelo [UNESP]; Ribeiro, Clovis Augusto [UNESP] (Springer, 2011)
The increase in sugarcane production and processing in order to obtain important products such as sugar and ethanol has the negative aspect of also increasing industrial residues. The most important residues originated during processing are bagasse, hydrolyzed bagasse, filter cake, vinasse, and ash. Thermal analysis revealed that these residues have peculiar properties, such as the presence of lignocellulosic material, except in the ash. The amount of organic matter decreases during the treatment process, due to the addition of chemical products to the residues, which are responsible for some alteration in their thermal properties. Colorimetric analysis showed considerable K and P concentrations in the vinasse and filter-cake residues. EDX and infrared spectroscopy showed the presence of Si in the residues. A higher percent of Si in ash sample was also observed, as a product of the thermal decomposition, by TG, FTIR, and X-ray diffractometry.
Keywords: Sugarcane; Residues; Thermal behavior; FTIR